Analityczne metody ustalania liczby skupień w rozmytych zbiorach danych - Migdał-Najman, Kamila; Najman, Krzysztof (Analytical procedures for determining the number of clusters in fuzzy data sets, 2006)
Several clustering techniques have been proposed for the analysis of fuzzy data sets. Cluster validity indices represent useful tools to support such a task. In this paper three validation indices were applied to fourteen data sets. The resultant optimal clusters have been found to be stable for the different validity indices used, viz. Bezdek’s Partition Coefficient (PC), Classification Entropy (CE) and Separation Index (S). It was shown that these methods might support the prediction of the optimal cluster partitioning for those data sets but the determination of the optimal number of clusters is an open problem. Two indices (PC and CE) were called into question their usefulness. Index S was characterized by relatively not large errors and significant effectiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 159-167